Magnitude and Characteristics of Occupational injury in Kombolcha textile factory, North East Ethiopia - Yessuf, Serkalem S; Moges, Haimanot Gebrehiwot; Ahmed, Ansha N (International Journal of Occupational Safety and Health, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–> Background: Working environment is one of the factors which can determine public health conditions as many workers spend a large portion of their time at work. Objective: The aim of this study was to assess the magnitude and characteristics of occupational injury among workers in Kombolcha textile factory, North East Ethiopia. Methods: Institution based cross-sectional study design was conducted from April1-15, 2013 among 455 randomly selected workers after stratification by working departments. A structured questionnaire based interview, review of records of injury report and walk through survey using work environment observation checklist were used to support the self-reported information. Descriptive statistics were used for analysis using SPSS version 20. Results: The overall occupational injury prevalence rate was 36.9%. Puncture, abrasion/laceration, fracture, cut and back pain were the most common types of injury. Most of the sources of injury were due to machinery, lifting heavy objects, splinters, fall and hand tools. Conclusion: The magnitude of occupational injury at Kombolcha textile industry showed a high prevalence that indicates the need to work on integrated injury prevention by mainstreaming occupational health and safety procedures in all working departments of the factory. DOI: http://dx.doi.org/10.3126/ijosh.v3i2.8381 <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; –> <!–[endif] –>